Lógica entre el mendigo y el pasajero del transporte público. un acercamiento desde el psicoanálisis (2017)
In this research, an approximation is made to the coordinates that allow to raise the logic that it raises between beggars and passengers of public transport, this from the point of view of the similarities and differences that arise in agreement with the capitalist discourse. This was done through open interviews with passengers and non-participant observation of beggars engaged in the practice of direct begging.